Qualitative Analysis of Test-to-Treat Benefits and Barriers for Pharmacists in Rural Washington State - Bradley Brown; Megan Undeberg; Angela Stewart; Kimberly McKeirnan (Pharmacy, 2025)
Background: Rural communities in the United States experience significant barriers in accessing healthcare, including inadequate numbers of providers and local healthcare facilities. These barriers are exacerbated during seasons with high rates of respiratory diseases when rural clinics and providers may be overwhelmed. When mild, many of these respiratory diseases may be managed effectively in alternate settings, including community pharmacies. Investigators interviewed pharmacists in Washington State to explore the capacity of pharmacists and pharmacies to provide test-to-treat services for COVID-19, influenza, and strep throat. Methods: A qualitative study design was used to conduct key informant interviews with pharmacists who precepted student pharmacists from a local university. Twenty interviews were conducted, transcribed, and qualitatively evaluated to identify themes. The 5 A’s of Access were utilized as a theoretical framework. This framework describes five domains of access, including affordability, availability, accessibility, accommodation, and acceptability. Results: Qualitative analysis identified several themes that described the benefits of offering test-to-treat services in rural communities, such as reducing geographical barriers to accessing care, reducing wait times for patients, and reducing the number of patients seeking higher levels of care for basic treatments. Barriers to offering test-to-treat services identified by pharmacist participants included difficulties with receiving payment for services, challenges with adequate staffing, and the lack of awareness among many people in rural communities that pharmacies offer test-to-treat services. Conclusions: Rural communities experience challenges with the limited capacity of healthcare providers to meet the needs of patients in their communities. The results of this qualitative analysis may be useful to pharmacists in U.S. states where collaborative drug therapy agreements or collaborative practice agreements allow the provision of test-to-treat services. By providing test-to-treat services, pharmacists can increase access to care for rural patients and alleviate the burden of offering these services from other healthcare providers.